n+(n-6)-2=-10

Simple and best practice solution for n+(n-6)-2=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+(n-6)-2=-10 equation:


Simplifying
n + (n + -6) + -2 = -10

Reorder the terms:
n + (-6 + n) + -2 = -10

Remove parenthesis around (-6 + n)
n + -6 + n + -2 = -10

Reorder the terms:
-6 + -2 + n + n = -10

Combine like terms: -6 + -2 = -8
-8 + n + n = -10

Combine like terms: n + n = 2n
-8 + 2n = -10

Solving
-8 + 2n = -10

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2n = -10 + 8

Combine like terms: -8 + 8 = 0
0 + 2n = -10 + 8
2n = -10 + 8

Combine like terms: -10 + 8 = -2
2n = -2

Divide each side by '2'.
n = -1

Simplifying
n = -1

See similar equations:

| 2/3+x/2-5=x/3+1 | | x+y=3280 | | -b-1=-9 | | 2/3/120 | | 9/z=5/11 | | 3n-10=n+4 | | -9b^2-7b-8=0 | | -3[2x-7]-2x+6= | | w=120-2(10+2w) | | -2/3(-3)(-7) | | -2(-7k-7)=2(8k+11) | | 3x+4-2x-7-4x=3 | | 12x+237x=68 | | 10x-2.67-4x=6x | | N/5-1=-7 | | 15(t-3)+3t=6(3t+5)-11 | | y=4.2x+7.9 | | -10=-w/2 | | 9x^2-6x+3x-2=0 | | 5=z/4-3 | | 3(2n+8)+2N=48 | | (-6)-3(2x+4)=18 | | k-4/2=10 | | 3(1+7x)=66 | | 20/2/3x+12 | | 9/10=-5/3b | | 6x-5+7=34 | | 9(x-5)= | | 4(-6-9p)=12(p+10) | | 2x+4=-(-7x+7) | | m-5=-14 | | 7x=-3-5x |

Equations solver categories